PERANCANGAN DAN PENGEMBANGAN MESIN ROASTING BIJI KOPI SEMI OTOMATIS YANG ERGONOMIS UNTUK USAHA UKM KOPI DENGAN MENGGUNAKAN PENDEKATAN ANTROPOMETRI - Eddi Indro Asmoro; Christian J.P. (Jurnal Ilmiah Dinamika Teknik, 2021)
Design and development of semi-automatic coffee bean roasting machines based on field conditions at Babah Kaca SMEs and Omah Gayeng SMEs, Salatiga. Basically the condition of the equipment used in Glasses UKM and Omah Gayeng UKM is not ergonomic. The method used is an anthropometric and ergonomic approach and uses work posture analysis using the RULA (rapidupper limb assessment) method. Anthropometric data used in this design are elbow height in a sitting position, forward arm span, and popliteal height. The data that has been obtained is then processed and the process of testing data uniformity, testing data adequacy, and determining percentiles is carried out. In this study the results of the design of a semi-automatic coffee roasting machine that has been adjusted and leveled at the dimensions of the body. Analysis of the work posture included in the RULA method. RULA method measurement is performed again when using roasted coffee machines, has a score of 3 which means it has a small risk level, a tool that is needed by workers in the process of roasting coffee beans and has the desired level of maturity.